(untitled) (Educational Dimension, 2025)
In the article, taking into account the challenges of the global information revolution, modern socio-educational realities, the authors substantiate the need for a communicative approach in teaching physics as one of the methodological approaches of a new scientific direction – psycho didactics of physics. The purpose of the article is defined as the coverage of some results of experimental teaching of physics to high school students of a secondary school based on a communicative approach with elements of bilingualism, its essence is characterized. Using a specific example, the author’s methodology for implementing this approach was first demonstrated, the need for its integration with other psycho-didactic approaches with the aim of comprehensive development of the student’s personality in the process of teaching physics is emphasized. Some experimental data are presented that make it possible, as a first approximation, to optimistically evaluate the results of testing the methodology of the communicative approach with elements of bilingualism in physics education, the prospect of further studies to obtain data on a more voluminous statistical sample is outlined , as well as to identify the possibility of using the proposed methodology in studying other disciplines in natural sciences in both secondary and high school.